Four new species of Isoneuromyia from China (Diptera: Keroplatidae) - Xu, Huachao; Cao, Jian; Wu, Hong; Evenhuis, Neal L.; Zhou, Zuji (Zootaxa, 2007)
Four new species of the genus Isoneuromyia Brunetti are described from China: I. sinica Xu, Cao et Evenhuis, n. sp; I. completa Xu, Cao et Evenhuis, n. sp; I. singulus Xu, Cao et Evenhuis, n. sp; I. wolongensis Xu, Cao et Evenhuis, n. sp. Another species, I.semirufa (Meigen) is newly recorded from Zhejiang province in China. A key to Chinese species of Isoneuromyia is given.